2020
DOI: 10.36419/jkebin.v11i2.375
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Pemberian Asi Eksklusif Di Posyandu Balita Kalingga Banyuanyar Surakarta

Abstract: Background: Breastfeeding is one of the most effective ways to ensure the health and survival of children. The scope of exclusive breastfeeding for infants aged 0-6 months fluctuates. The results by The Indonesian Demographic and Health Surveyshowed that the coverage of exclusive breastfeeding was 52% in 2017. Efforts to increase breastfeeding contributed to the achievement of reducing infant mortality and reducing the prevalence of malnutrition in children under five.Objective: This study aims to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
1
0
2
Order By: Relevance
“…In the educational variable, a value is obtained Prevenance Rosio (PR) is 1,360, this indicates that mothers who have primary education are 1,360 times more likely not to exclusively breastfeed compared to mothers who have further education. This is in line with the research conducted (Rakhmawati &;Utami, 2020), that there is a relationship between education and exclusive breastfeeding behavior. In this study, it was found that there was a relationship between education and exclusive breastfeeding behavior, because some mothers took basic education as many as 36 mothers (83.7%).…”
Section: B Bivariat Analysis the Relationship Between Education And E...supporting
confidence: 91%
“…In the educational variable, a value is obtained Prevenance Rosio (PR) is 1,360, this indicates that mothers who have primary education are 1,360 times more likely not to exclusively breastfeed compared to mothers who have further education. This is in line with the research conducted (Rakhmawati &;Utami, 2020), that there is a relationship between education and exclusive breastfeeding behavior. In this study, it was found that there was a relationship between education and exclusive breastfeeding behavior, because some mothers took basic education as many as 36 mothers (83.7%).…”
Section: B Bivariat Analysis the Relationship Between Education And E...supporting
confidence: 91%
“…Berdasarkan analisis bivariat dalam penelitian ini didapatkan bahwa Hasil penelitian ini senada dengan penelitian Rakhmawati N, Puji Utami RD (2020) tentang faktor-faktor yang mempengaruhi pemberian ASI eksklusif di Posyandu balita Kalingga Banyuanyar Surakarta melaporkan bahwa ada hubungan yang bermakna antara dukungan suami dengan pemberian ASI eksklusif di Posyandu Balita Kalingga Kelurahan Banyuanyar Surakarta (Rakhmawati, 2020). Penelitian selanjutnya oleh Novita E, Murdiningsih M, Turiyani T (2021) tentang faktor-faktor yang mempengaruhi pemberian ASI eksklusif di Desa Lunggaian Kecamatan Lubuk Batang Kabupaten OKU tahun 2021 bahwa dari hasil uji statistic Chi-Square antara variabel dukungan suami dan pemberian ASI eksklusif bahwa terdapat hubungan dukungan suami dengan pemberian ASI eksklusif (Novita, 2022).…”
Section: Dukungan Keluargaunclassified
“…Selain itu penelitian yang dilakukan Utami dkk, juga menyatakan bahwa terdapat hubungan antara dukungan suami terhadap determinan keberhasilan pemberian ASI Eksklusif dengan nilai P Value 0,007 (Anggraini et al, 2020). Penelitian ini juga didukung dengan penelitian yang dilakukan Nur Rakhmawati dkk, 2020 dimana terdapat hubungan antara dukungan suami dengan pemberian ASI Eksklusif dengan nilai P Value 0,028 (Rakhmawati & Utami, 2020). Dengan demikian dukungan suami mempunyai peran penting dalam keberhasilan pemberian ASI Eksklusif.…”
Section: Pembahasanunclassified